The roles of withdrawal in the negotiator personality-tactic relationship - Chow, Pui Ting; Cheung, Sai On; Young, Chiu Yan; Wah, Chi Kit (Journal of Business Economics and Management, 2015)
The personality of a negotiator shall affect his choice of tactics. Moreover, mixed predictions of the personality-tactic relationship have been derived from prior studies. One possible explanation is the influence of other intervening factors. In this regard, this study examines the role of withdrawal, as an intervening variable, in the negotiator personality-tactic relationship. State of withdrawal refers to the level of interest to continue with a negotiation. In a state of complete withdrawal, the interest to continue no longer exists and breakdown of the negotiation is inevitable. With the participation of practicing professionals, an experiment was used to collect data for the study. It was found that competitors are prone to withdraw and use more distributive tactics. However, this pattern changes with the composition of the dyad. If the negotiating counterpart is a cooperator, a competitor will adopt a more integrative approach. This finding reminds the importance of the personality factor in selecting members of a negotiating team.